2019
DOI: 10.1002/cmdc.201800724
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Replication by Targeting the Molecular Chaperone Hsp90: Synthesis and Biological Evaluation of 4,5,6,7‐Tetrahydrobenzo[1,2‐d]thiazole Derivatives

Abstract: Cellular chaperones that belong to the heat‐shock protein 90 (Hsp90) family are a prerequisite for successful viral propagation for most viruses. The hepatitis C virus (HCV) uses Hsp90 for maturation, folding, and modification of viral proteins. Based on our previous discovery that marine alkaloid analogues with a 4,5,6,7‐tetrahydrobenzo[1,2‐d]thiazole‐2‐amine structure show inhibition of HCV replication and binding to Hsp90, a series of twelve novel compounds based on this scaffold was designed and synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that HCV replication could be inhibited by targeting the host cell protein Hsp90. Preliminary work Lillsunde et al 218 found that compounds with a pyrrolamide and 4,5,6,7-tetrahydrobenzo[1,2-d] thiazole structure could inhibit the replication of HCV type 1b. It was found that compounds containing the unsubstituted 2-amino group had the most effective biological activity in terms of drug SAR.…”
Section: Anti-viral (Hcv) Activitymentioning
confidence: 99%
“…Previous studies have shown that HCV replication could be inhibited by targeting the host cell protein Hsp90. Preliminary work Lillsunde et al 218 found that compounds with a pyrrolamide and 4,5,6,7-tetrahydrobenzo[1,2-d] thiazole structure could inhibit the replication of HCV type 1b. It was found that compounds containing the unsubstituted 2-amino group had the most effective biological activity in terms of drug SAR.…”
Section: Anti-viral (Hcv) Activitymentioning
confidence: 99%
“…We have previously reported that 4,5,6,7-tetrahydrobenzo[d]thiazoles that were originally designed as DNA gyrase B inhibitors can suppress hepatitis C virus replication, which appears to involve their binding to Hsp90 [50,51]. Two other well-known DNA gyrase B inhibitors, novobiocin and coumermycin A1, also show inhibitory activities against Hsp90 and virus replication [52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…The microscale thermophoresis assay has been previously reported [50,51]. The well-known Hsp90 inhibitor 17-DMAG was included as the positive control.…”
Section: Microscale Thermophoresis For Binding To Hsp90βmentioning
confidence: 99%
“…SARS-CoV-2 has shown greater similarity with other viruses with regard to a need for host HSP90 protein, a non-conventional class purine utilizing enzyme, as a chaperone for viral proteins, helping prevent proteasomal degradation. Targeting HSP90 could inhibit replication of Kaposi sarcoma-associated herpesvirus (KHSV) (100) hepatitis C virus (HCV) (101) and also the human coronaviruses MERS-CoV and SARS-CoV (102). In a similar manner, ex vivo experiments involving transcriptomic profiling of SARS-CoV-2 infected human cell lines have shown that HSP90 inhibition impaired viral replication and activation of proinflammatory genes in primary human airway epithelial cells (103).…”
Section: Sars-cov-2 Interactions With the Purinomementioning
confidence: 96%